SIRT7 and the DEAD-box helicase DDX21 cooperate to resolve genomic R loops and safeguard genome stability - Song, Chenlin; Hotz-Wagenblatt, Agnes; Voit, Renate; Grummt, Ingrid (Genes & development, 2017)
R loops are three-stranded nucleic acid structures consisting of an RNA:DNA heteroduplex and a “looped-out” nontemplate strand. As aberrant formation and persistence of R loops block transcription elongation and cause DNA damage, mechanisms that resolve R loops are essential for genome stability. Here we show that the DEAD (Asp-Glu-Ala-Asp)-box RNA helicase DDX21 efficiently unwinds R loops and that depletion of DDX21 leads to accumulation of cellular R loops and DNA damage. Significantly, the activity of DDX21 is regulated by acetylation. Acetylation by CBP inhibits DDX21 activity, while deacetylation by SIRT7 augments helicase activity and overcomes R-loop-mediated stalling of RNA polymerases. Knockdown of SIRT7 leads to the same phenotype as depletion of DDX21 (i.e., increased formation of R loops and DNA double-strand breaks), indicating that SIRT7 and DDX21 cooperate to prevent R-loop accumulation, thus safeguarding genome integrity. Moreover, DDX21 resolves estrogen-induced R loops on estrogen-responsive genes in breast cancer cells, which prevents the blocking of transcription elongation on these genes.